Service on Registered Companies: Some Recent Developments in Malaysia - Balan, P. (Journal of Malaysian and Comparative Law, 1986)
Some recent decisions on the subject of service of a writ on a company registered under the Companies Act 1965 are of significance to the Malaysian practitioner and are considered as worthy of this short note.